Teachers’ perceptions and practices regarding to teaching the inductive approach to teaching grammar – A case study at a Hanoi-based university = Điển cứu về nhận thức và thực tế giảng dạy của giáo viên đối với đường hướng dạy ngữ pháp quy nạp tại một trư - Nguyễn, Thị Điệp (University of Languages and International Studies, 2017)
M.A. Thesis. English Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2013